2012
DOI: 10.4314/afrrev.v6i3.5
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Environmental Disclosures in the Nigerian Manufacturing Industry: A Study of Selected Firms

Abstract: The state of the world"s environment and the impact of mankind on the ecology of the world have led to increased public concern and scrutiny of the operations and performances of organisations. Despite some variations among countries in different regions, corporate environmental disclosures have increased globally in both size and complexity over the past two decades. Some developed countries have initiated mandatory disclosures in the reporting requirements. However, in most developing countries, environmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 12 publications
2
11
0
Order By: Relevance
“…Perhaps the most striking finding was the lack of environmental reports, which is consistent with Uwalomwa & Jimoh (2012) who observed that environmental reports among the selected listed companies in Nigeria was relatively low. Sahore & Verma (2017) revealed the prevalence of a general lack of emphasis on environmental reports in Indian companies.…”
Section: Corporate Social Responsibility Reporting Quantity Analysissupporting
confidence: 85%
See 1 more Smart Citation
“…Perhaps the most striking finding was the lack of environmental reports, which is consistent with Uwalomwa & Jimoh (2012) who observed that environmental reports among the selected listed companies in Nigeria was relatively low. Sahore & Verma (2017) revealed the prevalence of a general lack of emphasis on environmental reports in Indian companies.…”
Section: Corporate Social Responsibility Reporting Quantity Analysissupporting
confidence: 85%
“…Belal (2001) illustrated that CSRR of 30 Bangladesh companies largely emphasised on positive news. Uwalomwa & Jimoh (2012) indicate that about 57% of selected manufacturing companies in Nigeria concentrated more on positive disclosures rather than negative and neutral news at 18% and 24% respectively. Cunningham (2001) demonstrated that companies provide little negative SED even when they have experienced several negative social/environmental events.…”
Section: Discussionmentioning
confidence: 99%
“…The need for sustainable environmental cost management in the oil and gas sector has thus become the concern and focus of most nations and responsible corporate managements the world over. Organizations are now expected to be able to demonstrate that they are aware and addressing the impact of their operations on the environment and society in general [8].…”
Section: Introductionmentioning
confidence: 99%
“…Related topics have been researched in this area, but notable amongst them is (Uwaigbe, 2012) on corporate environmental disclosures in Nigerian manufacturing industry. The paper adopted the use of content analysis of manufacturing industry concerning the extent of disclosure.…”
Section: Empirical Reviewmentioning
confidence: 99%